Exploring the'socio' of socio-legal studies - Feenan, Dermot (Houndmills, Basingstoke, Hampshire, UK : Palgrave MacMillan, 2013)
'In this insightful collection, a broad range of scholars analyzes a core issue for socio-legal studies, what is understood by the'socio' of the'socio-legal'. Drawing from legal theory, cultural studies, and social policy, the collection's wide scope of themes and topics provides an important stock-take and analysis of the socio-legal field'--
Exploring the'Socio' of Socio-Legal Studies / Dermot Feenan -- What Makes a Social Science of Law? Doubling the Social in Socio-Legal Studies / Susan S. Silbey -- The Contested Social / John Clarke -- Law, Ethics and Socio-history : The Case of Freedom / Alan Norrie -- De Lege Ferenda : What is the'Socio' of Legal Reasoning? / Panu Minkkinen -- Reimagining the Humanities : Socio-Legal Scholarship in an Age of Disenhancement / Julia J.A. Shaw -- Transnational Legal Processes and the (Re)construction of the'Social : The Case of Human Trafficking / David Nelken -- Addressing a'Globalised Social' : Mobilization of Law in Global Networks with Reference to Biofuel Production in Indonesia / Jacqueline Vel and Adriaan Bedner -- Social Practice and Socio-Legal Studies / Hilary Sommerlad -- The Gendered'Socio' of Socio-Legal Studies / Rosemary Hunter -- Queer Sociality / Sally R. Munt -- Bringing Society to Law : A Critically Raced Accounting / Francisco Valdes -- From Responsible Saver to Stewarded Investor? / Sally Wheeler.
Includes bibliographical references and index.
Keywords: Sociological jurisprudence